Performance Analysis and Quality of Service for Video Streaming in Vehicular Adhoc Networks - Hussein Ali Al-Gubouri; Ayat Abbas Fadhil; Hajir A. Alzubaydi (المجلة الدولية للحاسبات والمعلوماتية, 2026)
Although safety applications have been the main driving force behind the development of Vehicular Ad-hoc Networks (VANETs), non-safety applications can also greatly benefit vehicular networks. Video streaming services, among non-security applications, can offer appealing features to many users and draw a large number of users. However, the adoption of video services in vehicular networks is challenging due to the high mobility characteristics of VANETs and packet loss during communication blackouts. This research is unique in the field of software-defined networks that examined a video streaming service’s effectiveness to investigate how well a video on demand service would work for users in vehicles on a highway. The packet loss caused by network reconfiguration during handoffs and its impact on the quality of the video transmitted have both been examined. With the help of SDN technology, we were able to maintain uninterrupted video streaming between vehicles in a vehicular ad hoc network.